Spatial variability of production and bromatological composition of Brachiaria and Panicum according to the soil chemical attributes in a silvipastoral system with eucalyptus - Mário, Nilton Eugénio [UNESP]; Corrêa, Adriany Rodrigues [UNESP]; Montanari, Rafael [UNESP]; Silva, Tatiane Carla; dos Santos, Anderson Secco (State University of Mato Grosso do Sul, 2024)
The variability of the soil chemical attributes in an area where woody crops are integrated with forage is quite complex, so it is important to understand the distribution of these soil attributes and their correlation with the forage yield. This study aimed to analyze the spatial variability of the production and bromatological composition of Brachiaria and Panicum forage species according to the soil chemical attributes when cultivated in a silvopastoral system integrated with eucalyptus to optimize the forage yield and nutritional quality of the forage in this multiple-use system. The study was conducted in the municipality of Ribas do Rio Pardo (MS) in the 2011/2012 crop season, where linear and spatial correlations were analyzed between attributes of eucalyptus, forage plants, and the chemical attributes of a Neossolo Quartzarênico (pH, organic matter (OM) and organic carbon (OC) contents, and carbon stock (CS)) at two soil layers: 0.00-0.10 and 0.10-0.20 m. A geostatistical grid with 72 sample points was used. Spatially, eucalyptus height can be estimated by cokriging with OM, and cellulose by cokriging with pH. OM contents above 6 g cm-3 indicated sites with the highest eucalyptus heights. On the other hand, pH values below 4.3 indicated sites with the highest cellulose content for the forage plants. Using geostatistics is technically feasible for creating specific management zones in the eucalyptus forage silvopastoral system.
Variabilidade espacial da produção e composição bromatológica de Brachiaria e Panicum em função dos atributos químicos com eucalipto em sistema silvipastoril
Keywords: Forest sustainability; Geostatistics; Soil management and conservation